Risk factors for coronary atherosclerotic heart disease in postmenopausal women: a meta-analysis - Miao, Xin; Wu, Lixing; Wang, Kuiyue; Wang, Yuhan; Zhang, Linlin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCoronary atherosclerotic heart disease (coronary heart disease; CHD) is the leading cause of death in women worldwide, and the number of patients and deaths is increasing each year. Approximately 3.8 million women die from CHD every year globally. After menopause, estrogen levels decrease, and the risk of cardiovascular disease increases substantially; however, research on risk factors for CHD in postmenopausal women has been inconclusive.ObjectiveTo systematically evaluate the risk factors for CHD in postmenopausal women.MethodsThe PubMed, Embase, Web of Science, CINAHL, CBM, CNKI, and VIP databases were searched up to February 9, 2024, for studies on risk factors for CHD in postmenopausal women. Two researchers independently screened the literature, extracted data, and evaluated the quality of the included literature. STATA17.0 software was used for meta-analysis.ResultsNine studies involving 29,4103 patients were included. The results of the meta-analysis showed that history of six or more pregnancies (hazard ratio = 1.538, 95% confidence interval: 1.241%–1.906%) was significantly associated with risk of CHD (P < 0.05).ConclusionMultiple pregnancies are associated with CHD incidence and related mortality in postmenopausal women. In the future, more and higher quality studies are needed to further verify this conclusion.